Geospatial Water Productivity Index (WPI) for rice - Kamal, Md. Rowshon; Mohd Soom, Mohd Amin; Mohamed Shariff, Abdul Rashid (Universiti Putra Malaysia Press, 2012)
A GIS-based user-interface programme was developed to compute the geospatial Water Productivity Index (WPI) of a river-fed rice irrigation scheme in Northwest Selangor, Malaysia. The spatial analysis includes irrigation blocks with sizes ranging from 20 to 300 ha. The amount of daily water use for each irrigation block was determined using irrigation delivery model and stored in the database for both main season (August to December) and off season (February to May). After cut-off of the irrigation supply, a sub-module was used to compute the total water use including rainfall for each irrigation block. The rice yield data for both seasons were obtained from DOA (Department of Agriculture, Malaysia) of the scheme. Then, the Water Productivity Index (WPI) was computed for each irrigation block and spatial thematic map was also generated. ArcObjects and Visual Basic Application (VBA) programming languages were used to structure user-interface in the ArcGIS software. The WPI, expressed in terms of crop yield per unit amount of water used (irrigation and effective rainfall), ranged from 0.02 to 0.57 kg/m3in the main season and 0.02 to 0.40 in off season among irrigation blocks, respectively. The development of the overall system and the procedure are illustrated using the data obtained from the study area. The approach could be used to depict the gaps between the existing and appropriate water management practices. Suitable interventions could be made to fill the gaps and enhance water use efficiency at the field level and also help in saving irrigation water through remedial measures in the season. The approach could be useful for irrigation managers to rectify and enhance decision-making in both the management and operation of the next irrigation season.